THE CONCEPT OF THE DIGITAL ECONOMY, ITS SIGNIFICANCE AND DEVELOPMENT TRENDS - Qodirov Azamatjon Bakhodirovich (American Journals, 2023)
This article discusses the concept of digital economy, its role in management and its importance in achieving economic prosperity. Also, some statistical data obtained from open sources are presented, and based on them, an attempt is made to explain why the use of digital technologies is important. In addition, at the end of the article, an attempt is made to give an understanding of "artificial intelligence" and to shed light on why it is important.
Keywords: economy, digital economy, digital technologies, human capital, effective use of resources, artificial intelligence.